Is Electronic Access to Medical Records an Empowering and Patient-centered Initiative? – a Qualitative Contextual and Linguistic Analysis of Danish Electronic Records - Hansen, Martha Monrad; Zethsen, Karen Korning (HERMES - Journal of Language and Communication in Business, 2018)
Political correctness demands a patient empowering and patient-centered approach to health care and today patients are increasingly involved in, and responsible for, their own health. Patients are potentially subjected to large amounts of health information and, in a Danish context, patients have recently gained easy electronic access to their hospital records. Access, which used to be by application, is now only a few clicks away. This initiative is praised as patient empowering and patient-centered even though the e-records are not written for patients, but are the working tool of health professionals. Thus, an expert language text, as it stands, has to function as patient information. In this article, we examine the language of the e-records with a view to determining potential lay-friendliness and thus patient-centeredness. We also discuss whether access, by definition, is a progressive initiative and whether patient empowerment is always the same as patient-centeredness.